The evolution of the local innovation agents (ALI) program methodology and its contribution to the innovation management at Medicatriz Dermocosmetics - Marengo, Lívia Luize; Soares, Allan Nunes; Romão, Henrique Rafael da Silva; Araújo, Davi Lucas Arruda de; Zilber, Silvia Novaes (REGEPE Entrepreneurship and Small Business Journal, 2022)
Objective: evaluate the influence of participation in cycles of the ALI Program in the innovative ambience of Medicatriz Dermocosmetics from 2013 to 2020. Investigated context: the basis of the ALI Program methodology was defined by eight premises: concrete results; use of indicators; results for Sebrae and the innovation ecosystem; involvement of the company’s team; collective construction of solutions; tools; companies motivated to innovate; and ALI as a facilitator to overcome the dilemma of having a good creative potential, but without converting into innovations that provide increased sales. Intervention: adopt mechanisms to solve the diagnosed problems, some interventions of open innovation, co-creation, branding, ethnographic research, current customer, and employee satisfaction were proposed for each cycle of participation. Results: in the first cycle, eleven new products were launched using nanotechnology and sensory transversality; in the second, there was a sub-category of customers and humanized projects for customers, employees, and social circles; in the third, remodeling of workshops, creation of paid courses, school visits, supervised internship, and advanced support; and in the fourth, a model for recognizing employees was created. Conclusion: the promotion of the continued practice of innovation actions in small companies and contributions to Medicatriz permeated the four dimensions of innovation. The company understands that investment in human development increases the chances of organizations becoming productive and engaging for their employees, suppliers, and customers.